The Meaning of Oral Tradition in Wedding Traditions in Nagan Raya Regency, Aceh Province - Yulsafli Yulsafli (ELS Journal on Interdisciplinary Studies in Humanities, 2022)
The purpose of this study is to describe the oral tradition in marriage customs in Nagan Raya District, Aceh Province. The problem method in this thesis is the historical method or the historical method with a qualitative descriptive approach. Sources of data used in this study are residents who are in the district of Nagan Raya, Aceh Province. In this study, the subjects were several villages in Nagan Raya district (Nagan Raya residents, parents who understand local customs and Sheikh ca'e and sheikh pantun seumapa). Data collection techniques in this study were observation, interviews, and documentation techniques. The results of data analysis show that there are several positions in the marriage customs of Nagan Raya district, Aceh Province, namely the manoe pucok, in which the procession includes the peusijuk process and watering by family and close relatives for linto baroe or dara baroe. As for the rhyme process, the one who leads is the sheikh from both sides, which also begins with bismillah and shalawat to the prophet Muhammad SAW.